Mutational diversity and hot spots in the alpha-sarcoglycan gene in autosomal recessive muscular dystrophy (LGMD2D). Issue 6 (June 1997) - Carrié, A; Piccolo, F; Leturcq, F; de Toma, C; Azibi, K; Beldjord, C; Vallat, J M; Merlini, L; Voit, T; Sewry, C; Urtizberea, J A; Romero, N; et al.
Abstract : Sarcoglycanopathies are a genetically heterogeneous group of autosomal recessive muscular dystrophies in which the primary defect may reside in any of the genes coding for the different partners of the sarcolemmal sarcoglycan (SG) complex: the alpha-SG (LGMD2D at 17q21.2), the beta-SG (LGMD2E at 4q12), the gamma-SG (LGMD2C at 13q12), and the delta-SG (LGMD2F at 5q33). We report a series of 20 new unrelated families with 14 different mutations in the alpha-SG gene. Along with the mutations that we previously reported this brings our cohort of patients with alpha-sarcoglycanopathy to a total of 31 unrelated patients, carrying 25 different mutations. The missense mutations reside in the extracellular domain of the protein. Five of 15 missense mutations, carried by unrelated subjects on different haplotype backgrounds and of widespread geographical origins, account for 58% of the mutated chromosomes, with a striking prevalence of the R77C substitution (32%). The severity of the disease varies strikingly and correlates at least in part with the amount of residual protein and the type of mutation. The recurrent R284C substitution is associated with a benign disease course.